Rancang Bangun Sistem Informasi Manajemen Inventaris Sekolah di SMA Negeri 6 Solok Selatan - Adia, Aldeki; Huda, Yasdinul (MASALIQ, 2025)
The manual inventory management system in schools presents various challenges, such as low efficiency, accuracy, and transparency in asset recording and reporting. This study aims to design and implement a web-based School Inventory Management Information System at SMA Negeri 6 Solok Selatan to support more effective and systematic inventory data management. Employing the Waterfall software development method and the Unified Modeling Language (UML) approach, the system was designed based on data collected through user observation and interviews, and functionally tested. The system was developed using the Laravel framework, PHP programming language, and MySQL database. The results show that the system successfully digitizes the entire process of inventory recording, storage, monitoring, and reporting. Features such as data search, asset grouping, and periodic reports facilitate inventory teachers in performing their tasks more efficiently and accurately. Moreover, the system enhances transparency and accountability in school asset management. In conclusion, the implementation of this information system significantly contributes to improving the quality of inventory management and is recommended as a digital solution for other schools facing similar challenges.